Alteration of ROS Homeostasis and Decreased Lifespan in S. cerevisiae Elicited by Deletion of the Mitochondrial Translocator FLX1. (7th May 2014) - Giancaspero, Teresa Anna; Dipalo, Emilia; Miccolis, Angelica; Boles, Eckhard; Caselle, Michele; Barile, Maria
Abstract : This paper deals with the control exerted by the mitochondrial translocator FLX1, which catalyzes the movement of the redox cofactor FAD across the mitochondrial membrane, on the efficiency of ATP production, ROS homeostasis, and lifespan of S. cerevisiae . The deletion of the FLX1 gene resulted in respiration-deficient and small-colony phenotype accompanied by a significant ATP shortage and ROS unbalance in glycerol-grown cells. Moreover, the f l x 1 Δ strain showed H2 O2 hypersensitivity and decreased lifespan. The impaired biochemical phenotype found in the f l x 1 Δ strain might be justified by an altered expression of the flavoprotein subunit of succinate dehydrogenase, a key enzyme in bioenergetics and cell regulation. A search for possible cis -acting consensus motifs in the regulatory region upstream SDH1-ORF revealed a dozen of upstream motifs that might respond to induced metabolic changes by altering the expression of Flx1p. Among these motifs, two are present in the regulatory region of genes encoding proteins involved in flavin homeostasis. This is the first evidence that the mitochondrial flavin cofactor status is involved in controlling the lifespan of yeasts, maybe by changing the cellular succinate level. This is not the only case in which the homeostasis of redox cofactors underlies complex phenotypical behaviours, as lifespan in yeasts.